The performance of Al2O3 crude oil on nonlinear stretching sheet - M. Fayyadh, MOHAMMED; Kandasamy, R.; Mohammed, RADIAH; Abdul Abbas Abbood, JAAFAR (2018)
Nanotechnology has enticed a good attention in boosting base fluid such as crude oil. A mathematical model is investigated to study MHD Carreau crude oil based Al2O3 nanofluids. Analysis over stretching sheet surface is illustrated that include consideration of nanoparticles shape with high (E1=5.0) and low (E1=0.0) electric field. Depending on nanoparticle shape, deferent expects of nanofluids flow such that the shapes as (sphere, cylinder, lamina) to boost the heat and mass transfer. Employing convenient self-similar transformation, the set of partial differential equation converted to dimensionless system. These equations has numerically solution by apply Runge-Kutta Fehlberg form plus so-called shooting technique and solving algebraically in Maple 18. Effect of relevant parameters on all concerned profile are incurred to examine the heat and mass transfer properties. For thermal radiation and heat generation parameters the profiles are on negative worth of temperature, is seen in the out of boundary region all these physical behaviours are due to the combined effects of the viscosity and density of the crude oil. The result obtained that heat generation, Brownian motion and magnetic field hit a dominant role on Al2O3 - crode oil . The investigation revealed that there is no important role for nanoparticle shapes on Al2O3 crude oil.